PENGUATAN LITERASI SAINS MELALUI PEMBELAJARAN BERBASIS SOCIO- SCIENTIFIC ISSUES DALAM BIOLOGI - Eka Fitriasari; Usman Usman; Dian Rachmawati (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2026)
The low achievement of Indonesian students' scientific literacy as reflected in PISA results calls for innovation in biology learning. This study aims to analyze the improvement of high school students' scientific literacy through the implementation of Socio-Scientific Inquiry-Based Learning (SSI-BL) on environmental change material. This study employed a pre-experimental method with a one group pretest-posttest design conducted at SMA Negeri 1 Kabupaten Tangerang. The sample consisted of 30–35 students selected using purposive sampling technique. The instrument used was a scientific literacy test combining multiple choice and essay questions covering three aspects: science knowledge, science competence, and science context. Data were analyzed using paired sample t-test and N-Gain test. The results showed a significant improvement in scientific literacy with a Sig. (2-tailed) value of 0.000 < 0.05. The mean pretest score of 41.33 increased to 70.33 on the posttest. The overall N-Gain value was 0.44 in the moderate category, with science knowledge at 0.59 (moderate), science competence at 0.49 (moderate), and science context at 0.25 (low). These findings indicate that SSI-BL is effective in improving students' scientific literacy and can serve as an innovative and contextual alternative model for biology learning.